2014
DOI: 10.4103/2152-7806.140199
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Thiel cadaveric model for MRI-guided stereotactic procedures in neurosurgery

Abstract: Background:Magnetic resonance imaging (MRI)-guided deep brain stimulation (DBS) and high frequency focused ultrasound (FUS) is an emerging modality to treat several neurological disorders of the brain. Developing reliable models to train and assess future neurosurgeons is paramount to ensure safety and adequate training of neurosurgeons of the future.Methods:We evaluated the use of Thiel cadaveric model to practice MRI-guided DBS implantation and high frequency MRI-guided FUS in the human brain. We performed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 33 publications
1
10
0
Order By: Relevance
“…12(a), the MR image shows that the selected cadaver had good brain volume and well-preserved architecture, allowing for a clear differentiation between grey and white matter prior to intervention. This agrees with the characteristics of the MRI scans of soft-embalmed cadavers reported by Eljamel et al [35] and Gueorguieva et al [36]. After placing the cadaver in the supine position, a burr hole ~1 cm in diameter was created in the skull in the midpupillary line (above pupil) 2.5 cm from midline and 1 cm in front of the coronal suture (Kocker's point) as the opening of the intraoperative path for the needle transducers.…”
Section: Wire Phantom Scansupporting
confidence: 88%
“…12(a), the MR image shows that the selected cadaver had good brain volume and well-preserved architecture, allowing for a clear differentiation between grey and white matter prior to intervention. This agrees with the characteristics of the MRI scans of soft-embalmed cadavers reported by Eljamel et al [35] and Gueorguieva et al [36]. After placing the cadaver in the supine position, a burr hole ~1 cm in diameter was created in the skull in the midpupillary line (above pupil) 2.5 cm from midline and 1 cm in front of the coronal suture (Kocker's point) as the opening of the intraoperative path for the needle transducers.…”
Section: Wire Phantom Scansupporting
confidence: 88%
“…Kerckaert et al said that in future studies they will apply Thiel´s techniques for fixation of the central nervous system. Eljamel et al (2014) did some imaging studies of Thiel embalmed cadavers with MRI, revealing a good imaging with clear differentiation of white and gray matters, that suggested that it was a very good preservation of the brain. To prove what Thiel said about the good flexibility and plasticity preservation in organs and tissues, several authors studied the biomechanical properties.…”
Section: Description Of the Thiel Methods And Its Variantsmentioning
confidence: 99%
“…Ando et al (2014) analyzed the validity of estimating fascicle length in the vastus lateralis and intermedius of the quadriceps by ecography, concluding that quality of echographic images of Thiel-embalmed cadavers is equivalent to the quality of images obtained from living human beings. Eljamel et al (2014) suggest that long-term use of these cadavers (up to 15 months) makes the Thiel embalmed cadaver an excellent model for any other computer-assisted image-guided, minimally-invasive neurosurgery for training, such as DBS insertion. They consider that Thiel embalmed cadavers can be used for developing and testing various stereotactic functional neurosurgical procedures Kerckaert et al reported the results of the creation of the Endogent center, a center for anatomy and invasive techniques at the University of Ghent, Belgium, publishing their work experiences and uses of the Thiel embalming technique.…”
Section: Authorsmentioning
confidence: 99%
“…In addition to the successful application on histopathology, fixed and preserved tissue is also served as a useful tool for clinical training and biomedical instrumentation design (McLeod et al, 2010;Eljamel et al 2014). In this case it is not only the tissue morphology that need to be considered but also its mechanical properties since they have significant influence to the design and performance of such instruments.…”
Section: Introductionmentioning
confidence: 99%
“…In this case it is not only the tissue morphology that need to be considered but also its mechanical properties since they have significant influence to the design and performance of such instruments. Fixation induced mechanical property changes have attracted attention and studies have been carried out to investigate the effects of tissue preservation methods on the mechanical properties of different kinds of tissues using traditional mechanical loading methods (McLeod et al, 2010;Eljamel et al 2014;McElhaney et al 1964;Sedlin, 1965;Goh and Ang, 1989;Tan et al, 2002;Kikugawa and Asaka, 2005). However, to the best of our knowledge there are some limitations regarding to the current studies of the fixation effects to mechanical properties of tissue: 1) the traditional loading method cannot provide real time elasticity change since it is a relatively time consuming technique, thus the detailed elasticity change with precise time line during the fixation procedure cannot be determined; 2) the degree of influence of different fixation methods to mechanical properties in relation to different kinds of tissues remains unknown.…”
Section: Introductionmentioning
confidence: 99%